2021
DOI: 10.3389/fphar.2021.739615
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Attenuates Cardiac Hypertrophy by Inhibiting Mitochondrial Dysfunction Through SIRT3/PARP-1 Pathway

Abstract: Cardiac hypertrophy is an important characteristic in the development of hypertensive heart disease. Mitochondrial dysfunction plays an important role in the pathology of cardiac hypertrophy. Recent studies have shown that sirtuin 3 (SIRT3)/poly (ADP-ribose) polymerase-1 (PARP-1) pathway modulation inhibits cardiac hypertrophy. Quercetin, a natural flavonol agent, has been reported to attenuate cardiac hypertrophy. However, the molecular mechanism is not completely elucidated. In this study, we aimed to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Most recently, Quercetin was identified as SIRT3 activator. It was shown to preserve mitochondrial function and structure, ameliorate cardiac hypertrophy, and improve overall cardiac function via activation of the SIRT3 in spontaneously hypertensive rats (156).…”
Section: Modulators Of Sirt3mentioning
confidence: 99%
“…Most recently, Quercetin was identified as SIRT3 activator. It was shown to preserve mitochondrial function and structure, ameliorate cardiac hypertrophy, and improve overall cardiac function via activation of the SIRT3 in spontaneously hypertensive rats (156).…”
Section: Modulators Of Sirt3mentioning
confidence: 99%
“…Several studies have evaluated the cardioprotective effects of quercetin in an SHR model. Quercetin and its metabolites effectively reduce an increase in blood pressure and heart rate [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] and improve left ventricular [ 62 , 65 , 66 ] and renal hypertrophy [ 62 ]; it enhances the endothelium-dependent aortic vasodilation induced by acetylcholine [ 54 , 57 , 59 , 62 , 63 , 67 , 68 ], but had no effect on the endothelium-independent response induced by nitroprusside [ 54 , 63 , 68 ]. Quercetin also reduces mesenteric contractions in response to phenylephrine, which is associated with depolarization and an increase in smooth muscle intracellular calcium concentration [ 54 , 57 , 58 , 68 , 69 ]; these results suggest that this flavonoid is able to provide vascular protection by ameliorating endothelial dysfunction in a hypertensive model.…”
Section: Quercetinmentioning
confidence: 99%
“…Furthermore, Chen et al reported that quercetin ameliorated the hypertrophic response such as increased mRNA levels of atrial natriuretic factor and β-myosin heavy chain induced by Ang-II in H9C2 cells. The flavonoid was also able to protect against mitochondrial dysfunction by modulation of the sirtuin 3 /poly (ADP-ribose) polymerase-1 pathway, adding to the protective effects against cardiac hypertrophy [ 66 ]. Honcharov et al reported that quercetin treatment leads to significantly improved morphological and functional parameters of the heart by inhibiting trypsin-like and chymotrypsin-like proteasome activities in the aorta and trypsin-like, and peptidyl-glutamyl peptide-hydrolyzing-like activities in the heart [ 71 ].…”
Section: Quercetinmentioning
confidence: 99%
“…Persistent hypertrophy leads to cardiac decompensation and systolic dysfunction and exacerbates ventricular remodeling, leading to HF [220]. Multiple natural small molecules treat cardiac hypertrophy through different targets [186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202]; for example, quercetin protects mitochondrial function and inhibits cardiac hypertrophy through SIRT3/PARP-1 signaling [182,184,186,188]. Triptolide increased CDK1 and CDK4 mRNA, CDK1, p21 and p27 mRNA expression [185].…”
Section: Myocardial Hypertrophymentioning
confidence: 99%